Taxonomic Tapestries: The Threads of Evolutionary, Behavioural and Conservation Research - Behie M, Alison (ANU Press, 2015)
This volume explores the complexity, diversity and interwoven nature of taxonomic pursuits within the context of explorations of humans and related species. It also pays tribute to Professor Colin Groves, whose work has had an enormous impact on this field. Recent research into that somewhat unique species we call humankind, through the theoretical and conceptual approaches afforded by the discipline of biological anthropology, is showcased. The focus is on the evolution of the human species, the behaviour of primates and other species, and how humans affect the distribution and abundance of other species through anthropogenic impact. Weaving together these three key themes, through the considerable influence of Colin Groves, provides glimpses of how changes in taxonomic theory and methodology, including our fluctuating understanding of speciation, have recrafted the way in which we view animal behaviour, human evolution and conservation studies.